From Learners to Entrepreneurs: A Study on the Inclination of University Students Towards Entrepreneurship as a Career Option and the Role of Education - Aaijaz, Naila; Bin Ibrahim, Dahlan; Ahmad, Ghazali (Prabandhan: Indian Journal of Management, 2012)
This study investigates the inclination of students of Universiti Malaysia Kelantan pursuing their graduation in entrepreneurship studies towards entrepreneurship. Specifically, the paper aims to examine the relationship between entrepreneurship education and university student’s inclination towards entrepreneurship. This study also examines the moderating effects of demographic characteristics and family business background on budding entrepreneurs undergoing entrepreneurship education. A self administered questionnaire was used in this study to collect data on the sampling population. Descriptive analysis, factor analysis, multiple regression, one-way ANOVA, and independent sample t-test were used to test the hypothesized propositions. The results showed that the role of the university in promoting entrepreneurship had a statistically significant relationship with student’s inclination towards entrepreneurship.